Longitudinal analyses of Olympic athletics and swimming events find no gender gap in performance improvement - Kovalchik, S. A.; Stefani, R. (Journal of Quantitative Analysis in Sports, 2013)
Gender gaps in absolute performance at the Olympics are well-established, while gender differences in relative performance have not been considered. We analyzed time trends in male and female performance improvement for medal results in all individual athletics and swimming events in Olympic years with male and female competition. Performance improvement was defined as the percentage change in performance over the gold-medal result of the previous Olympic year. In mixed effects models that accounted for the effects of the order of finish, event, and year, we found a non-significant average difference in performance improvement of <0.5% for events in running, jumping, throwing, and swimming. Since the mid-twentieth century, the record at the Summer Games shows that gains in the performance of female Olympic medalists have kept pace with men.